Specialist Education and Development Research Model, Workload, Work Experience on Police Performance with Compliance as Intervening Variable: Validity and Reliability Test - Tien Yus Tini; Badiah Perizade; Isnurhadi Isnurhadi; Yuliani Yuliani; Sulastri Sulastri; Zunaidah Zunaidah (Universitas Dharma Wacana, 2022)
This study aims to analysis validity and reliability test of the effect specialist education and development, workload and work experience on the performance of police officers with Compliance as an intervening variable. The research was conducted at the South Sumatra Regional Police with a total population of 6,742 and a sample of 378 police officers serving in the South Sumatra work unit area. This study uses an analytical technique with an inferential statistical approach, statistical tools are used to solve multilevel models simultaneously which cannot be solved by linear regression equation in this study using the Structural Equation Model (SEM). The results of this study indicate that Based on the results of data estimation, the instrument is declared valid, because the magnitude of the loading factor is â‰¥ 0.50, so are the results of the reliability test using construct reliability with the provision that a construct or variable is said to be reliable with a CR value â‰¥ 0.70 and the variance extracted value with the condition > 0.5.